STRATEGI PEMASARAN THEANNA VILLA & SPA CANGGU DALAM MENGHADAPI COVID-19 - Ni Made Pramita Dewi; I Made Bayu Wisnawa; I Nengah Sandi Artha Putra; Ni Wayan Mekarini (Universitas Triatma Mulya, 2023)
This research discusses the impact of the Covid-19 pandemic on the tourism sector in Canggu, Bali, especially at Theanna Villa & Spa Canggu. This pandemic has caused a drastic drop in tourist visit rates and room occupancy rates in the area. Even the situation is low, Theanna Villa & Spa Canggu chose to continue operating by implementing a different marketing strategy to maintain its business. This study aims to analyze the marketing strategy implemented by villa management in dealing with the Covid-19 pandemic. Room occupancy rate data from March 2020 to August 2022 is used to see changes in room occupancy rates over that period. The research method used in this study is a qualitative descriptive research method. Data collection is done by interview, observation, and documentation. The research showed that Theanna Villa & Spa Canggu applies a marketing mix by compiling a marketing mix to deal with the Covid - 19 pandemic in order to increase room occupancy rates. The results of this study explain that there are obstacles faced by Theanna Villa & Spa Canggu in marketing their products during the Covid - 19 pandemic.